2007
DOI: 10.1016/j.jasms.2006.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of a snake venom using high mass detection MALDI-TOF mass spectrometry

Abstract: Proteomic profiling involves identification and quantification of protein components in complex biological systems. Most of the mass profiling studies performed with matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) have been restricted to peptides and small proteins (Ͻ20 kDa) because the sensitivity of the standard ion detectors decreases with increasing ion mass. Here we perform a protein profiling study of the snake venom Sistrurus miliarius barbouri, comparing 2D g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…The matrix molecules produce highly intense signals in the low-mass range (ϳ0 -1000 (6 ). The 3rd challenge in MALDI protein profiling is establishing the reproducibility of peak intensity.…”
mentioning
confidence: 99%
“…The matrix molecules produce highly intense signals in the low-mass range (ϳ0 -1000 (6 ). The 3rd challenge in MALDI protein profiling is establishing the reproducibility of peak intensity.…”
mentioning
confidence: 99%
“…In contrast, the mass spectrum obtained with the high mass HM1 detector contains many peaks up to m/z 50,000 ( Figure 1b). Several studies have established that the detection sensitivity of higher mass proteins using an MCP detector is highly attenuated in multi-component mixtures, due to detector saturation [14,17,24,25]. The tissues analyzed in a MALDI imaging and profiling MS analysis contain a very large number of proteins that will exacerbate this loss of sensitivity due to detector saturation.…”
Section: Resultsmentioning
confidence: 99%
“…A particular advantage of STJ detectors is that multiply charged ions can be distinguished on the basis of their higher kinetic energy. The higher detection efficiency and higher capacity of the STJ detector has been exploited for the analysis of complex protein mixtures: it was demonstrated that the STJ detector could detect multiple higher mass proteins that were not detected using an MCP [24]. Unfortunately the Comet Macromizer is no longer commercially available.…”
mentioning
confidence: 99%
“…Since its first description thirty years ago, twodimensional gel electrophoresis (2DE) has been the primary tool for detecting proteins in an organism and complex biological extracts (1,2). By separating proteins based on two independent parameters -pI values by isoelectric focusing (IEF) in one dimension and molecular mass by SDS-PAGE in the other -samples can be resolved to a few thousand protein spots (3).…”
Section: Introductionmentioning
confidence: 99%